Yoga as a Complementary Therapy for Social Media Generation's Well Being - Purva G. Sharma; Gopal Krishna Sharma (Dr. Chinmay Pandya, 2018)
Unlike past, preteens and teens today lead a mentally and emotionally charged life along with the exacting physical rigors of their daily life. Apart from sports, academics, parents and peers the mentioned age group is also spending a considerable amount of time in the virtual, digital world of social media connectivity along with its various appendages. Unregulated social media exposure often makes life a tightrope existence for these children and adolescents. Studies have shown that the increasing use of social media and technology is having a negative impact on the physical and mental health of children and teenagers by making them more prone to anxiety, depression, and other psychological disorders, as well as by making them more susceptible to future health problems. In this light of increased stress and health problems with growing social media usage, this paper reviews studies and proposes yoga as a mind-body alternative medicine intervention to improve physical and mental health conditions. It also highlights the efficacy of yoga as a complementary therapy enhancing overall wellbeing of children. After reviewing relevant available literature, we conclude that Yoga has the potential to be a promising complementary therapy for children and adolescents but more efforts are required to find most effective application and implementation methods for the same.